Analisis Penggunaan Youtube sebagai Media Ajar Pendidikan Anak Usia Dini di Era Digital - Nadya Zahra Amada; Arif Hakim (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Youtube has become a supplement for the development of students' knowledge and skills that can be made directly by the teacher. Many young children are already proficient at using gadgets to seek for entertainment through Youtube. X Kindergarten has implemented the use of Youtube as a teaching media since early 2020, because it is considered effective. The subjects of this study were the Teachers of Group A and the Principal of Kindergarten X. The type of approach used in this research is a qualitative approach with a case study method. The data collection techniques are through interviews, observation and documentation studies. The results of this study are in preparation for learning the teacher makes learning videos on Youtube by paying attention to the objectives of core and basic competencies, references, content that is suitable for early childhood and using Standard Operating Procedure for making Youtube. At the evaluation stage, it is done by reprocessing the activities or tasks presented in the Youtube learning video by re-asking the children and noticing the suitability of the task in its application. Abstrak. Media Youtube telah menjadi suplemen bagi pengembangan pengetahuan dan keterampilan siswa yang dapat dibuat langsung oleh guru. Banyak anak usia dini yang sudah mahir menggunakan gadget untuk mencari dan melihat hiburan melalui situs Youtube. Taman Kanak-kanak X menerapkan penggunaan Youtube sebagai media ajar sejak awal tahun 2020, karena dianggap efektif. Subjek penelitian ini adalah Guru Kelompok A dan Kepala Sekolah Taman Kanak-kanak X. Jenis pendekatan yang digunakan pada penelitian ini adalah pendekatan kualitatif dengan metode studi kasus. Adapun teknik pengumpulan data melalui wawancara, observasi dan studi dokumentasi. Hasil penelitian ini adalah pada persiapan pembelajaran guru membuat video pembelajaran dalam Youtube dengan memperhatikan tujuan pada KI dan KD, referensi, konten yang sesuai dengan anak usia dini serta menggunakan SOP pembuatan Youtube. Pada tahap evaluasi dilakukan dengan cara mengolah kembali kegiatan atau tugas yang disampaikan dalam video pembelajaran Youtube dengan bertanya kembali pada anak serta melihat kesesuaian tugas dalam pengaplikasiannya.